Perbandingan Latihan Sensorimotor dengan Pemulihan Fisik Konvensional dalam Meningkatkan Stabilitas Atlet Pasca Cedera - Pratama, Raditya; Zakaria, Achmad; Kusuma, Angga Indra; Ruman (MAN Insan Cendekia Jambi, 2025)
Sensory-motor training can improve body awareness and better control of body movements, making it important in the recovery of injured athletes. Although sensory-motor training is newer than conventional physical recovery, this approach is beginning to be applied in various rehabilitation clinics and training programs. This study used an experimental design with a quantitative approach involving two groups, each consisting of 6 athletes. A total of 12 athletes from Koni Kota Malang were selected from several selected sports, including soccer, basketball, and volleyball. Overall, the results of this study indicate that sensorimotor training can be an effective alternative in improving body stability, balance, and reaction time in athletes after injury. The results also provide further evidence that technology and methods that integrate sensorimotor aspects can help athletes in the post-injury recovery process. Therefore, it is important to consider the application of sensorimotor training in athlete rehabilitation programs.